Automatic video surveillance system - Cabigao, Maria Cecilia G.; Pineda, Mabel Joyce C.; San Buenaventura, Rachelle B.; Vallesteros, Eugene Martin H. (2003)
Video surveillance is a process that utilizes video and television equipment to be able to keep a cloase watch over a person or a place. An effective video surveillance system requires good equipment and manpower to perform the task of observing a scene. Human resources associated with this implementation may prove to be very expensive especially when the application demands 24-hour monitoring. The team proposes a system that aims to replace the needed manpower behind video surveillance. The implementation of an automatic video surveillance system is composed of three major modules: the discrimination of the foreground image from the background model, the segmentation of the foreground image into its constituent regions, and human motion analysis, which will be responsible for alerting the users of suspicious actions. These three parts involve computations that take up huge amounts of processing time. Therefore, in order not to sacrifice the real-time output generation as required by this project, several optimization technqiues must be employed. This paper details the implementation of the said system inclusive of the optimization techniques used with the ultimate goal of real-time motion detection and human motion analysis.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Video surveillance; Motion detection and analysis